Implementing a Learner-Centred Teaching Approach in the Field of Philology - Sazdovska Pigulovska, Milena (Institute of Knowledge Management – Skopje, 2017)
With the shift from the traditional approach to the functional approach to teaching many disciplines, teaching in the field of philology nowadays is also experiencing a shift from the traditional ways of teaching to a more innovative functional approach to teaching. In other words, applying a functional approach in the field of philology goes beyond the classical lecture-and-note approach and is mainly centred on interaction in the classroom and on creating a cooperative learning process. This is particularly applicable in translation studies which, inter alia, involve foreign language learning, translation, specialised terminology, cultural studies. etc. Translation studies is a discipline predominantly centred on practical experience as one of its fundamental pillars, where the application of an innovative and practical approach to teaching and learning is of crucial importance. The subject of research in this paper is the application of a learner-centred teaching approach in the higher education process in the Republic of Macedonia, with special emphasis on the field of philology, through practical implementation of innovative collaborative techniques in the classroom. The end results in this paper show that this approach, on the one hand, abandons a teaching style of excessive relying on the professor’s feedback and opinion (which is unproductive and more typical for the traditional approach), and, on the other hand, enables learning through real-life experience as well as through forming critical thinking and conducting research outside of the classroom. By implementing a learner-centred approach in the higher educational process the focus is put on student involvement and student cooperation, whereas the purpose of this paper is to demonstrate that its specific application in the field of philology is aimed at applying new methods of interactive and cooperative teaching and learning inside and outside of the classroom. In addition, this paper suggests creative classroom activities that contribute to creating an atmosphere conducive to (practical) learning, high level of direct student involvement and interaction, cooperation among students, student autonomy and motivation, and much needed hands-on experience, thus avoiding an unproductive and passive classroom. The results and conclusions at the end of the paper point out a need for replacing old and traditional methods of teaching and learning, and implementing more dynamic techniques and activities that stimulate active student involvement both in the process of learning and in decision-making about the way of learning and the course content. One of the fundamental conclusions presented in this paper is that interaction in the classroom is a two-way process that does not only involve collaboration with the professor, but above all collaboration among the students, whereas interaction is a key factor contributing to motivation and autonomy of students in the process of learning and research. Correspondingly, by applying specific inventive techniques analysed in this paper, students gradually start to see the process of learning as a bidirectional process as they become increasingly aware that knowledge should not only come from the professor, but that learning must also happen among students.
Keywords: Learner-centred approach, teaching methods, translation studies